Investigating the Relationship between Critical Thinking and Self -efficacy of Healthcare Managers of Ahvaz University of Medical Sciences - ahmad Peivand; azam alavi; Amin TorabiPour (Journal of Social Behavior and Community Health)
Background: Critical thinking and self-efficacy play an important role in achieving the workplace. This study aimed to determine the relationship between critical thinking and self-efficacy in healthcare managers of Ahvaz University of Medical Sciences. Methods: This descriptive correlational study was conducted on 115 healthcare managers affiliated to Ahvaz University of Medical Sciences using census sampling method in 2019. Data were collected using standard Ricketts' Critical Thinking Questionnaire and Sherer General Self-Efficacy Scale and were analyzed by descriptive and analytical statistics (Spearman correlation coefficient) using SPSS 24 software. Results: There was a significant relationship between mean scores of critical thinking and self-efficacy of health managers (P <0.001) and self-efficacy with the beta coefficient of 0.436 could significantly predict critical thinking. The mean critical thinking score of healthcare managers was 125.96±10.62, and the mean self-efficacy score of healthcare managers was 34.67±6. 87. Conclusion: According to the research findings, critical thinking has a direct and positive relationship with managers' self-efficacy. To apply these findings, it is recommended that authorities take necessary measures to strengthen and develop critical thinking among healthcare managers to establish a stronger foundation for enhancing their self-efficacy.